Reversible Splenial Lesion Syndrome developing in the setting of sleep deprivation: Reversible Splenial Lesion Syndrome developing in the setting of sleep deprivation - Onder, Halil; Akturk, Tulin; Sacmaci, Hikmet (Nepal Journal of Neuroscience, 2022)
In this report, we present a rare case of reversible splenial lesion syndrome which was etiologically associated with sleep deprivation. Up to our knowledge, there is no previous research reporting sleep deprivation as an inducer agent of RESLES. To elucidate our observation, future reports of larger case series are surely warranted. The clarification of the possible association between sleep deprivation and the reversible splenial lesion may also provide substantial perspectives regarding the mechanisms and health impact of sleep deprivation; the functional and pathophysiological role of the splenial corpus callosum in sleep physiology. Besides, we think that the awareness of this entity should increase among clinicians to avoid unnecessary investigations as the case in our patient.